SNS Online Victimization and Fear of Crime: Including the Moderating Effects of Disorder, Collective Efficacy, and Gender Difference - Lee, Seong-Sik (Victims & offenders, 2022)
This study aims to investigate the relationship between social network site (SNS) online victimization and fear of crime. It is well known that fear of crime is not only affected by the victimization experience in itself but also influenced by the online environment wherein individuals are involved in diverse SNS activities. Thus, the role of victimization on fear of crime is differentiated by the SNS environment, irrespective of whether it is well ordered or not. The research outcome based on the analysis of university students in Seoul, Korea clearly shows that the more they are victimized online and the higher the levels of online disorders, the more they exhibit fear of crime. However, online trust and informal social control, representing online collective efficacy, fail to show any significant effect on fear of crime. Regarding the role of male and female differences in these interaction processes between online victimization with disorder and collective efficacy, respectively, interesting and significant, albeit differentiating, outcomes are found between males and females. The interaction effect between online victimization and environment shows a mingled outcome for male, while it is wholly insignificant for female implying that victimization experience is sufficient to incur fear of crime.